The Effectiveness Of The Beelinguapp Application To Improve Efl Learners' Reading Comprehension On Narrative Text At Smkn I Cirebon: Efektivitas Aplikasi Beelinguapp Dalam Meningkatkan Pemahaman Membaca Siswa EFL Pada Teks Naratif Di SMKN I Cirebon - NurlaelaRahmawati; Dwi Nopiyadi; Lili Sururi Asipi (Tomorrow's Education Journal, 2024)
This study aims to assess the effectiveness of the Beelinguapp application in improving EFL students' reading comprehension of narrative texts at SMKN I Cirebon and to determine the benefits of implementing this technology in the learning process. English language skills are crucial both globally and within the Indonesian education system. EFL (English as a Foreign Language) learners often struggle with reading comprehension, a critical skill that involves various cognitive processes and understanding the meaning of texts. Narrative texts, which are engaging and rich in moral values, are favored by students. This research use a quantitative approach was employed using an experimental method with a pretest-posttest design and questionnaires. The study sample consisted of 60 students from Class X TEI 1 - TEI 4, selected through random sampling. Data collection techniques included a pretest, posttest, and questionnaire administered to the experimental group. The results indicated a significant improvement in reading comprehension, with a t-value of 8.029, which is greater than the t-table value of 2.022 (Sig. 2-Tailed = 0.000 < 0.05). Thus, the null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted, confirming that Beelinguapp positively and significantly impacts reading comprehension of narrative texts. Additionally, student feedback from questionnaires revealed cognitive improvements in learning outcomes, particularly in reading comprehension, after the application of the Beelinguapp in the learning process.